Omerta And Its Implications For Eradication Of Criminal Acts Of Corruption: Integration Of Maqasid Sharia (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2023)
Corruption is an extraordinary crime that has a systemic impact on social life, the nation, and the state. So the eradication process requires extraordinary measures. However, 24 years after the promulgation of the Corruption Eradication Law, criminal statistics show that corruption crimes are still high. This recorded is only a small part of the criminal acts of corruption that have not been criminally processed. Among the causal aspects is the legal system, especially legal substance. That was by disharmonization of these laws shows that there is an opportunity for the tradition of omerta by the perpetrators, namely the legitimacy of formal legal norms that replace Herziene Indlandsch Reglement. By another side of Islamic law criminal acts of corruption have an impact on the basic of worldly life as well as safety in the afterlife. So this research aims to provide a solution to eradicating criminal acts of corruption and elaborate on the Islamic legal system. The type of research was normative juridical with a qualitative approach by secondary data and meta norms regarding the Corruption Eradication Law and the Criminal Procedure Law. Research findings show that the culture of omerta occurs due to disharmonization of norms between the Corruption Eradication Law and Article 56 paragraph (1) of Law Number 8 of 1981 concerning Criminal Procedure Law which gives suspects or defendants the right not to answer questions from law enforcement officials at any stage. inspection. Then the omerta of criminal acts of corruption also contradicts the concept of maqasid sharia.